2004
DOI: 10.1097/01.qai.0000131937.52106.92
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic CD4+ Cell Depletion in Hepatitis C Virus/HIV???Coinfected Patients

Abstract: Coinfection with HIV and hepatitis C virus (HCV)-specific immune responses, increases hepatic inflammation, accelerates hepatic fibrosis, and is associated with deceased treatment responses. We quantified intrahepatic lymphocyte and hepatocyte phenotypes in HCV-infected patients with (n = 38) and without (n = 41) HIV infection. A single pathologist counted positive cells in 5 portal and 5 lobular areas. Coinfected patients had 6.81 +/- 1.9 fewer CD4 cells per portal field (10.58 +/- 1.12 vs. 4.97 +/- 1.09 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 23 publications
1
26
0
2
Order By: Relevance
“…We therefore considered whether the decreased CD4 + T cell percentages found in HCV/HIV-coinfected [21]. Thus, the present study confirms that these differences are found using a completely different approach.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We therefore considered whether the decreased CD4 + T cell percentages found in HCV/HIV-coinfected [21]. Thus, the present study confirms that these differences are found using a completely different approach.…”
Section: Discussionsupporting
confidence: 73%
“…Possible obstacles to identifying a relationship between these 2 parameters include inadequate sample size, the need to expand liver lymphocytes, and sampling error inherent in liver biopsies. It should be noted, however, that Canchis et al also found no association between liver CD4 + T cell frequencies enumerated in situ and liver disease stage in 38 HCV/HIV-coinfected subjects [21].…”
Section: Discussionmentioning
confidence: 97%
“…Tuyama et al [38 ] recently were able to demonstrate the possibility of HIV to directly infect hepatic stellate cells and induce enhanced collagen production in an in-vitro model. Immunostaining of liver biopsies demonstrated that HIV might enhance hepatocyte apoptosis [39] and proliferation [40], which could add to the higher risk for fibrosis progression in HIV/HCV-coinfected individuals. Interesting data on intrahepatic mRNA levels of cytokines and cellular markers that compares liver biopsies of HCV/HIV-coinfected patients with HCVmonoinfected ones was recently published [41].…”
Section: Molecular Pathologymentioning
confidence: 99%
“…One study that examined the global infiltrate of lymphocytes within the liver but not virus-specific T cells demonstrated a depletion of total intrahepatic portal CD4 T cells out of proportion to declines in peripheral counts [47]. This finding indicated that the inflammatory infiltrate in the liver is missing a key component of an effective T-cell response.…”
Section: Hiv Associated With An Increased Rate Of Fibrosis Progressionmentioning
confidence: 97%